Efektivitas Penerapan Posisi Orthopneic dalam Mengatasi Pola Napas Tidak Efektif pada Pasien Asma: Studi Kasus di Ruang Edelweiss RSUD Kardinah Tegal - Widiani, Zamila; Khasanah, Suci (NHM PRESS, 2025)
Asthma is a chronic inflammatory disease of the airways characterized by airway obstruction and ineffective breathing patterns. One non-pharmacological intervention that can help improve ventilation is the orthopneic position. This study aimed to determine the effectiveness of the orthopneic position in addressing ineffective breathing patterns in asthma patients. This research employed a descriptive case study design involving a 43-year-old female patient diagnosed with asthma and experiencing shortness of breath. The orthopneic position intervention was administered for three consecutive days, with each session lasting 15 minutes in the morning. Data were collected through observations of respiratory rate and clinical symptoms. The results showed a decrease in respiratory rate from 26 breaths per minute to 20 breaths per minute, along with improvements in clinical symptoms, including reduced wheezing and decreased use of accessory respiratory muscles. In conclusion, the application of the orthopneic position is effective in reducing respiratory workload and improving ventilation in asthma patients with ineffective breathing patterns.